Multiple substrate usage of Coxiella burnetii to feed a bipartite-type metabolic network - Häuslein, Ina; Cantet, Franck; Reschke, Sarah; Chen, Fan; Bonazzi, Matteo; Eisenreich, Wolfgang (Frontiers in Cellular and Infection Microbiology, 2017)
The human pathogen Coxiella burnetii causes Q-fever and is classified as a category B bio-weapon. Exploiting the development of the axenic growth medium ACCM-2, we have now used 13C-labeling experiments and isotopologue profiling to investigate the highly diverse metabolic network of C. burnetii. To this aim, C. burnetii RSA 439 NMII was cultured in ACCM-2 containing 5 mM of either [U-13C3]serine, [U-13C6]glucose, or [U-13C3]glycerol until the late-logarithmic phase. GC/MS-based isotopologue profiling of protein-derived amino acids, methanol-soluble polar metabolites, fatty acids, and cell wall components (e.g. diaminopimelate and sugars) from the labeled bacteria revealed differential incorporation rates and isotopologue profiles. These data served to decipher the diverse usages of the labeled substrates and the relative carbon fluxes into the core metabolism of the pathogen. Whereas de novo biosynthesis from any of these substrates could not be found for histidine, isoleucine, leucine, lysine, phenylalanine, proline and valine, the other amino acids and metabolites under study acquired 13C-label at specific rates depending on the nature of the tracer compound. Glucose was directly used for cell wall biosynthesis, but was also converted into pyruvate (and its downstream metabolites) through the glycolytic pathway or into erythrose 4-phosphate (e.g. for the biosynthesis of tyrosine) via the non-oxidative pentose phosphate pathway. Glycerol efficiently served as a gluconeogenetic substrate and could also be used via phosphoenolpyruvate and diaminopimelate as a major carbon source for cell wall biosynthesis. In contrast, exogenous serine was mainly utilized in downstream metabolic processes, e.g. via acetyl-CoA in a complete citrate cycle with fluxes in the oxidative direction and as a carbon feed for fatty acid biosynthesis. In summary, the data reflect multiple and differential substrate usages by C. burnetii in a bipartite-type metabolic network, resembling the overall topology of the related pathogen Legionella pneumophila. These strategies could benefit the metabolic capacities of the pathogens also as a trait to adapt for replication under intracellular conditions.